Improved 3D image segmentation for X-ray tomographic analysis of packed particle beds. (November 2015) - Wang, Y.; Lin, C.L.; Miller, J.D.
Highlights: Segmentation of particle boundaries improved using feature-based classification. Excellent 3D image quality can be achieved with high fidelity. Segmentation of mineral particles accomplished using only one training data set. Abstract: Although High Resolution X-ray Micro Tomography (HRXMT) has been developed in the past years for the 3D analysis of multiphase mineral particles in packed particle beds, image analysis of fine and/or high-density/high atomic number particles has been limited by existing segmentation algorithms. In this regard, a feature-based segmentation algorithm has been developed and demonstrated to provide a more accurate image processing method for the analysis of such multiphase particle populations. Based on this improved segmentation algorithm, image analyses of packed particle bed samples were compared to segmentation by traditional 3D watershed segmentation. Also, calculation of particle number using optical microscopy, together with a digital camera, was accomplished to validate feature-based segmentation. Detailed procedures and results for sample preparation, image analysis and validation are presented and discussed.